Maintenance ERP Risk management for the Service Industry case study: Hajj and Pilgrimage Organization - khozouie, Nasim; Farjami, Yaghoob; Rafighi, masoud (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
In recent decades, a lot of company across the world have implementedERP systems. Although ERP implementation is a more explored issue, But even ERP implementation ï¬nished satisfactorily, success in ERP adoption is notguaranteed. It depends on the effectiveness process in thepost-implementation ERP systems.There are critical success factors in these projects. In this paper we evaluate critical Risk factor after ERP implementation at Service Industry,especialyHajj and Pilgrimage Organization.